2019
DOI: 10.1002/joc.6313
|View full text |Cite
|
Sign up to set email alerts
|

Regional analysis of trend and non‐stationarity of hydro‐climatic time series in the Southern Alborz Region, Iran

Abstract: Analysis of the trend of climatic records is necessary for better climate modelling and subsequently adopting effective planning and management strategies. In this research, the Southern Alborz Range, Iran was selected to analyse the trends and stationarity of hydro‐climatic time series. The Mann–Kendall (M‐K) classic test was considered to identify the monotonic trend, while trend free pre‐whitening approach was applied for eliminating serial correlation from the time series. Meanwhile, time series stationari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 66 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The relative and standalone tests were also used for this purpose. Autocorrelation analysis was applied in precipitation time series to remove any autocorrelation before trend analysis [43][44][45][46], as autocorrelation affects the trend results. Autocorrelation values were calculated with a 95% confidence interval for precipitation data.…”
Section: Dataset and Preprocessingmentioning
confidence: 99%
“…The relative and standalone tests were also used for this purpose. Autocorrelation analysis was applied in precipitation time series to remove any autocorrelation before trend analysis [43][44][45][46], as autocorrelation affects the trend results. Autocorrelation values were calculated with a 95% confidence interval for precipitation data.…”
Section: Dataset and Preprocessingmentioning
confidence: 99%
“…The results revealed that the reference evapotranspiration time series in Iran contained unit root and were not stationary. Similarly, Mirdashtvan et al (2020) applied KPSS test on various hydro-climatic variables such as precipitation, mean air temperature and pan evaporation in Iran.…”
Section: Stationarity Testmentioning
confidence: 99%
“…Given these facts, it is necessary to understand the impact of climate change on the hydrology, as well as evaluate trends and their magnitude in the temporal series. Many researchers have used classic trend detection models, such as the Mann-Kendall test; for correlating the magnitude of trends using the Rho Spearman test; and the Pettitt test, widely used for the analysis of abrupt changes in a hydroclimatic series (Tamagnone et al, 2019;Ferreira et al, 2020;Mirdashtvan et al, 2020;Salehi et al, 2020). These studies report urbanization, population growth, and the rise of agricultural land as the main factor behind the changes in the statistical patterns of the hydro climatological series.…”
Section: Introductionmentioning
confidence: 99%